2015
DOI: 10.1007/s10865-015-9665-y
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic associations between cancer-related stress and fruit and vegetable consumption among colorectal cancer patients and their family caregivers

Abstract: This study examined how stress from cancer affects fruit and vegetable consumption (FVC) in cancer patients and their family caregivers during the year following diagnosis. Colorectal cancer patients and their caregivers (92 dyads) completed questionnaires at two (T1), six (T2), and 12 months post-diagnosis (T3). Individuals reported perceived cancer-related stress (CRS) at T1 and days of adequate FVC at T1 through T3. Both patients and caregivers reported inadequate FVC during the first year post-diagnosis. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Much of the previous research evaluating the health behaviors of patients with cancer has focused on people with earlier stage disease or did not analyze data by stage of disease. Furthermore, few studies of cancer patients examined the behavior patterns of their family caregivers (Bellizzi et al, 2005;Demark-Wahnefried et al, 2005;Patterson et al, 2003;Shaffer et al, 2016). Data in the present study appear similar to other studies of cancer survivors of early stage disease or all-stages combined.…”
Section: Health Behaviors Of Advanced Cancer Patients and Their Caregsupporting
confidence: 84%
See 1 more Smart Citation
“…Much of the previous research evaluating the health behaviors of patients with cancer has focused on people with earlier stage disease or did not analyze data by stage of disease. Furthermore, few studies of cancer patients examined the behavior patterns of their family caregivers (Bellizzi et al, 2005;Demark-Wahnefried et al, 2005;Patterson et al, 2003;Shaffer et al, 2016). Data in the present study appear similar to other studies of cancer survivors of early stage disease or all-stages combined.…”
Section: Health Behaviors Of Advanced Cancer Patients and Their Caregsupporting
confidence: 84%
“…In studies enrolling primarily early-stage survivors, there are a few notable exceptions. For example, a recent study found relationships between fruit and vegetable consumption among people with colorectal cancer and their cancer caregivers in the year following diagnosis (Shaffer et al, 2016). In one of the first intervention studies of its kind, Winter-Stone and colleagues (2016) found positive outcomes for prostate cancer survivors and wives who participated in an exercise program.…”
Section: Introductionmentioning
confidence: 99%
“…Stress can affect eating habits and may be shown in the consumption of vegetables. A study by Shaffer et al (47) found that cancer-related stress was associated with a low consumption of vegetables among cancer-patients and their caregivers. Nutritional guidance can help increase the use of products rich in fibre and vitamins (48).…”
Section: Discussionmentioning
confidence: 99%
“…Median sample size in these 71 quantitative studies was 224.5 (Interquartile Range 354). Most of the studies were conducted in breast cancer survivors (n = 25, 35.2%) [26,28,29,32,[35][36][37][38]40,[42][43][44]50,51,61,[64][65][66]68,70,80,87,90,93,94], five studies were conducted in prostate cancer survivors [73,74,85,89,92], six in colorectal cancer survivors [33,34,49,63,72,96], two in lung cancer survivors [52,95], two in head and neck cancer survivors [55,71], one in in thyroid cancer survivors [79], one in laryngology cancer survivors [54], one in endometrial cancer survivors [27], and one in hematologic cancer survivors [69]. 27 studies (38%) were conducted in survivors of mixed cancer types [30,31,…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The duration of these interventions ranged from four weeks [81,82] to four years [51]. 18 out of 71 quantitative studies (i.e., 25.4%) were prospective observational studies [29,30,44,49,52,61,[63][64][65][66]71,72,80,85,87,[93][94][95].…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%